HIGH RELIABILITY ANTI-BACKGROUND ILLUMINATION ALGORITHM FOR MEASURING ENERGY ILLUMINATION PRODUCED BY A BACTERICIDAL IRRADIATOR - DOBROVOLSKY, YURY; LIPKA, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A significant problem when measuring a useful information signal transmitted by means of optical radiation by telecommunication systems in natural conditions is background lighting. It creates optical interference that distorts the useful optical informative signal transmitted and significantly reduces the reliability of such a telecommunication system. Therefore, counteracting background interference caused, in particular, by solar radiation, is an urgent task both for telecommunication systems and for software engineering, with the help of which it is also possible to counteract optical interference. At the same time, both the hardware part of the device and the software must have a certain level of reliability. In particular, this problem is relevant when measuring the intensity of ultraviolet radiation with a wavelength of 254 nm, which is created by bactericidal lamps in medical institutions. To solve the above-mentioned problem, an analysis of existing methods of countering background radiation when measuring the intensity of UV radiation was carried out. It is shown that the best of the existing methods is the use of a photo signal processing scheme based on automatic gain adjustment and the use of appropriate light filters. A reliable algorithm for measuring a weak optical signal at the level of 0.1 μW/cm2 at a wavelength of 254 nm, in the conditions of background illumination of the photodiode by solar radiation, is proposed by selecting only that fraction of the photocurrent that is generated during the time interval set by the appropriate software. The operation of the proposed algorithm, implemented with the help of an appropriate electrical circuit and specialized reliable software, was studied. It is shown that the scheme provides measurement of energy illuminance from 0,1 μW/cm2 at illuminance up to 20,000 lux, which allows us to consider that the proposed scheme is sun-blind. The reliability of the circuit and the software that supports it was investigated by fail-safe tests. The general fluctuations of the calibrated value of energy illumination during 500 hours of operation vary from 295 to 310 μW/cm2, which does not exceed 5.1%. The probability of error-free operation of the software for eight hours of operation was 94%.